Optimizing the exposure in minimally invasive mitral surgery: a new left atrial retractor system - Greco, Ernesto; Rose, David; Irace, Francesco; Frati, Giacomo (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Optimal exposure of the mitral valve is paramount in minimally invasive surgery (MIS) and a prerequisite for successful mitral valve repair or replacement. We report the concept of a new left atrial retractor (Karl Storz GmbH, Tuttlingen, Germany) dedicated to MIS. The effectiveness of the device was evaluated in a prospective series of 40 patients successfully operated at our institution.